Sprint Acceleration Mechanics in Fatigue Conditions: Compensatory Role of Gluteal Muscles in Horizontal Force Production and Potential Protection of Hamstring Muscles - Edouard, Pascal; Mendiguchia, Jurdan; Lahti, Johan; Arnal, Pierrick J.; Gimenez, Philippe; Jiménez-Reyes, Pedro; Brughelli, Matt; Samozino, Pierre; Morin, Jean-Benoit (Frontiers in Physiology, 2018)
Aim: Hamstring muscle injury is the main injury related to sports requiring sprint acceleration. In addition, hamstring muscles have been reported to play a role in horizontal force production during sprint acceleration performance. The aim of the present study was to analyse (i) the determinants of horizontal force production and (ii) the role of hip extensors, and hamstring muscles in particular, for horizontal force production during repeated sprint-induced fatigue conditions. Method: In this expertimental laboratory setting study including 14 sprint-trained male athletes, we analysed (i) the changes in sprint mechanics, peak torque of the knee and hip extensors and flexors, muscle activity of the vastus lateralis, rectus femoris, biceps femoris and gluteus, and sagittal plane lower limb motion, before and after twelve 6-second sprints separated by 44 seconds rest on an instrumented motorised treadmill, and (ii) the determinants of horizontal force production (FH) during the sprint acceleration in a fatigue state (after 12 sprints). Results: The repeated-sprint protocol induced a decrease in Pmax (-17.58.9%; effect size (ES):1.57, large) and in FH (-8.68.4%; ES:0.86, moderate) but not meaningful changes in FTot (-3.42.9%; ES:0.55, small) and FV (-3.13.2%; ES:0.49, small). A decrease was found in concentric peak torque of the knee flexors and extensors and in gluteus and vastus lateralis muscle activity during entire swing and end-of-swing phase. An increase was found in contact time and swing time, while step frequency and knee speed before ground contact decreased. Muscular determinants associated with FH and its decrease after the repeated-sprint protocol were concentric peak torque of the hjp extensors (p=0.033) and a decrease in gluteus maximus activity at the end-of-swing (p=0.007), respectively. Conclusion: Sprint-induced fatigue lead to changes in horizontal force production muscular determinants: hamstring muscle seems not to have the same role than in non-fatigue condition. Horizontal force production seems to be more dependent on the hip extensors and gluteus maximus function. Given the fatigue-induced decrease in hamstring muscle strength, we can hypothesise that muscle compensatory and kinematic strategies reported in a fatigued state could be an adaptation to allow/maintain performance and a protective adaptation to limit hamstring muscles constraints.